2021
DOI: 10.25259/ijdvl_359_2021
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of topical amphotericin B in 30% dimethyl sulfoxide cream versus 30% dimethyl sulfoxide cream for nondermatophyte onychomycosis treatment: A pilot study

Abstract: Background: Although topical amphotericin B cream is effective for the treatment of nondermatophyte mold onychomycosis in vitro, studies of its effectiveness and safety in vivo are limited. Objectives: We studied the effectiveness and safety of topical 0.3% amphotericin B in 30% dimethyl sulfoxide cream (amphotericin B cream) in nondermatophyte mold onychomycosis using the vehicle cream 30% dimethyl sulfoxide cream as control. Methods: This randomized controlled study was conducted between January 2019 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“… 150,151 Despite showing a moderate to high MC rate (56.2%–89.2%), topical amorolfine 5% treatment resulted in only moderate clinical improvement (50%; Table 5). 150,151 Topical amphotericin B and topical luliconazole were efficacious, as shown with a limited number of patients 147,152 . Topical and oral combination therapies, such as amorolfine nail lacquer with oral itraconazole, may improve the likelihood of treatment response (Table 6).…”
Section: Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“… 150,151 Despite showing a moderate to high MC rate (56.2%–89.2%), topical amorolfine 5% treatment resulted in only moderate clinical improvement (50%; Table 5). 150,151 Topical amphotericin B and topical luliconazole were efficacious, as shown with a limited number of patients 147,152 . Topical and oral combination therapies, such as amorolfine nail lacquer with oral itraconazole, may improve the likelihood of treatment response (Table 6).…”
Section: Treatmentmentioning
confidence: 99%
“…146 Topical amphotericin B treatment has also shown promise in a limited number of studies (Tables 5 and 6). 140,147,148 Other potential treatments include ciclopirox nail lacquer, amorolfine 5% nail lacquer and efinaconazole 10% nail solution. 144,148,149 There is scarce information on effective treatment options for Neoscytalidium.…”
Section: Aspergillusmentioning
confidence: 99%
See 1 more Smart Citation
“…They have been reports of topical voriconazole cream and topical amphotericin B being effective in the treatment of non-dermatophyte mould onychomycosis. 91,92,114,115…”
Section: Newer Antifungal Agentsmentioning
confidence: 99%
“…There are no published results available. A randomised, double-blinded, phase IV study [ 24 ] demonstrated that Amphotericin B was effective when adults with non-dermatophyte onychomycosis were treated with a formulation containing 0.3 mg/mL of the drug in 30% dimethyl sulfoxide cream (DMSO, molecular formula C2H6OS). Dimethyl sulfoxide is a highly polar, water-soluble organic liquid that shows a variety of pharmacological activities [ 42 ] and is widely used as a chemical solvent and free radical scavenger.…”
Section: Topical Antifungal Nail Therapies Under Development and Inve...mentioning
confidence: 99%